The Representation of Hegemonic Femininity in TikTok Content: An Analysis of Beauty Standards and the Construction of Gender Identity - Hulpa Idayani (Lembaga Bale Literasi, 2025)
TikTok has evolved into a digital cultural space that plays a significant role in shaping gender representations through widely circulated visual content. This study aims to analyze the representation of hegemonic femininity in TikTok content and examine how the beauty standards portrayed contribute to the construction of users' gender identities. The research employs a qualitative approach using visual content analysis of ten TikTok videos from the beauty, glow-up, and aesthetic lifestyle categories that demonstrate high engagement rates and frequently appear on users’ For You Page (FYP). The analysis is conducted using Schippers’ theory of Hegemonic Femininity and Mansour Fakih’s concept of gender injustice. The findings reveal that hegemonic femininity is represented through the visual dominance of fair skin, slim body types, symmetrical facial features, flawless makeup, and aesthetic lifestyles, all of which are constructed as symbols of the ideal woman. These representations are reinforced by TikTok’s algorithmic mechanisms, which tend to promote content with specific visual characteristics, thereby contributing to the homogenization of beauty standards. The study also finds that digital beauty standards contribute to the internalization of dominant feminine values through practices of social comparison, the pursuit of public validation, and the formation of users’ self-image. Furthermore, various forms of gender injustice are identified, including stereotyping, marginalization, subordination, and symbolic violence, which emerge both in the representations themselves and in audience responses to women's bodies. This research highlights that TikTok functions not only as a platform for entertainment but also as a cultural agent that plays an active role in producing, reproducing, and sustaining the construction of hegemonic femininity in the digital era.